Managing fisheries for human and food security. Issue 1 (27th May 2013) - McClanahan, Tim; Allison, Edward H; Cinner, Joshua E
Abstract: We evaluate the current status of the global marine fisheries using the frameworks of conflict, food security and vulnerability. Existing trends suggest that there is likely to be greater food insecurity and fisheries conflicts due to issues such as: declining fishery resources; a North–South divide in investment; changing consumption patterns; increasing reliance on fishery resources for coastal communities; and inescapable poverty traps creating by low net resource productivity and few alternatives. Consequently, managing fisheries from a food security perspective will become increasingly necessary, and we therefore briefly review fisheries from the perspective of food security and evaluate it using a vulnerability framework. Specifically, we describe three key components of vulnerability (exposure, sensitivity and adaptive capacity) for selected fisheries. This is followed by proposals to build the adaptive capacity of fisheries and recommendations to avoid future conflicts. Adaptive capacity attributes include assets, social flexibility and organization attributes, and learning. We present some key ways to build these aspects of the fishery to reduce the many potential environmental and social threats that increase the vulnerability of fisheries. Recommendations include fewer subsidies, reduced capital investment, precautionary management to minimize risks of ecosystem collapse, conservation of remaining resources, diversified portfolios of production and markets, and greater equity in contracts and distribution. Further, we recommend a contextual diagnostic and environmental justice framework to assess a range of options for fishery governance.